Prevalence of post-concussion syndrome and associated factors among patients with traumatic brain injury at Debre Tabor Comprehensive Hospital, North Central Ethiopia - Teshome, Assefa Agegnehu; Ayehu, Gashaw Walle; Yitbark, Getachew Yideg; Abebe, Endeshaw Chekol; Mengstie, Misganaw Asmamaw; Seid, Mohammed Abdu; Molla, Yalew Melkamu; Baye, Nega Dagnaw; Amare, Tadeg Jemere; Abate, Agmas Wassie; Yazie, Taklo Semineh; Setargew, Kidist Hunegn (Frontiers in Neurology, 2022)
Introduction: The occurrence of three or more of the following signs and symptoms, such as headache, dizziness, exhaustion, irritability, sleeplessness, difficulties in concentrating, or memory problems, following a head injury is referred to as post-concussion syndrome (PCS). Even though post-concussion syndrome has not been studied in Ethiopia, the productive age group is frequently affected by health issues related to head trauma, which either directly or indirectly affect the growth of the nation. Objective: To assess the prevalence and associated factors of post-concussion syndrome among patients with traumatic brain injury at Debre Tabor Comprehensive hospital, Debre Tabor, North Central Ethiopia. Methods: A successive sampling technique was used to conduct a hospital-based cross-sectional study on 405 traumatic brain injury patients at Debre Tabor Comprehensive Hospital from January 1, 2022, to May 30, 2022. SPSS version 25 was used to analyze the data. The factors connected to post-concussion syndrome were found using bivariate and multivariable logistic regression analysis. Statistical significance was determined by a P-value of ≤ 0.05. Result: During the data collection period, 405 cases in total were interviewed, with a 98% response rate. More than half (60.7%) of patients were married, with the majority of patients (39.8%) falling between the ages of 18 and 29. At least three post-concussion syndrome symptoms were present in 42.8% of subjects. History of comorbidities, GCS levels of 8 or below, 9 to 12 at the time of presentation, brain neuroimaging findings, and having fair or poor social support were found to be substantially linked with PCS in multivariate logistic regression. Conclusion: About 41.5% of study participants had at least three symptoms of PCS. The Glasgow coma scale level at the time of presentation, the reason for the injury, social support, and the site of the injury were all significantly associated with the occurrence of PCS.